2016
DOI: 10.1113/jp271827
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic nucleotide regulation of cardiac sympatho‐vagal responsiveness

Abstract: Cyclic adenosine monophosphate (cAMP) and cyclic guanosine monophosphate (cGMP) are now recognized as important intracellular signalling molecules that modulate cardiac sympatho‐vagal balance in the progression of heart disease. Recent studies have identified that a significant component of autonomic dysfunction associated with several cardiovascular pathologies resides at the end organ, and is coupled to impairment of cyclic nucleotide targeted pathways linked to abnormal intracellular calcium handling and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 135 publications
(265 reference statements)
1
17
0
Order By: Relevance
“…Emerging evidence suggests oxidative stress leading to dysregulation of cyclic nucleotide signalling plays a major role behind the elevated Ca 2+ . These neurons show impaired nitric oxide (NO) - cGMP signalling resulting in lower cGMP levels and disinhibition of neurotransmission51525354. Moreover we recently reported that the neuronal Ca 2+ channel phenotype in the SHR is linked to a phosphodiesterase – cyclic nucleotide impairment and failure of cGMP signalling to inhibit I CaN 16.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests oxidative stress leading to dysregulation of cyclic nucleotide signalling plays a major role behind the elevated Ca 2+ . These neurons show impaired nitric oxide (NO) - cGMP signalling resulting in lower cGMP levels and disinhibition of neurotransmission51525354. Moreover we recently reported that the neuronal Ca 2+ channel phenotype in the SHR is linked to a phosphodiesterase – cyclic nucleotide impairment and failure of cGMP signalling to inhibit I CaN 16.…”
Section: Discussionmentioning
confidence: 99%
“…Several comprehensive articles (for a topical collection see The Journal of Physiology , June 2016) have reviewed various aspects of the neurocardiology of the autonomic nervous system, including the sophisticated regulation of its ‘proximal’ pre‐ganglionic section (Ardell & Armour, ; Habecker et al . ; Janig, ), brainstem and higher centres processing (Shivkumar & Ardell, ), and the role of cyclic nucleotide signalling in the modulation of sympatho‐vagal balance (Li & Paterson, ).…”
Section: Introductionmentioning
confidence: 99%
“…At the level of peripheral autonomic ganglia, alterations in cyclic nucleotide pathways are discussed in relation to neurotransmitter release (Kalla et al . ; Li & Paterson, ). Consequences for peripheral neural network control of cardiac electrical and mechanical function is presented with a primary focus on neural transduction of cardiac pathology relative to heart failure and arrhythmias (Ardell et al .…”
mentioning
confidence: 99%
“…At the level of the cardiomyocyte, alterations in excitation-contraction coupling, substrate utilization and receptor signalling are considered in normal vs. pathological conditions (Gloschat et al 2016). At the level of peripheral autonomic ganglia, alterations in cyclic nucleotide pathways are discussed in relation to neurotransmitter release (Kalla et al 2016;Li & Paterson, 2016). Consequences for peripheral neural network control of cardiac electrical and mechanical function is presented with a primary focus on neural transduction of cardiac pathology relative to heart failure and arrhythmias (Ardell et al 2016).…”
mentioning
confidence: 99%